Respondent driven sampling - Matthias Schonlau; Elisabeth Liebau (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2010)
Respondent driven sampling (RDS) is a network sampling technique typically employed for hard-to-reach populations (e.g. drug users, men who have sex with men, people with HIV). Similar to snowball sampling, initial seed respondents recruit additional respondents from their network of friends. The recruiting process repeats iteratively, thereby forming long referral chains. Unlike in snowball sampling, it is crucial to obtain estimates of respondents' personal network size (i.e., number of acquaintances in the target population) and information about who recruited whom. Markov chain theory makes it possible to derive population estimates and sampling weights. We introduce a new Stata program for RDS and illustrate its use.
Keywords: C83; C88; 330; survey methodology; Stata software; chain referral sampling